The viscosity of R32 and R125 at saturation - Oliveira, Carla Padrel de (2012)
This paper reports new measurements of the viscosity of R32 and R125, in both the liquid and the vapor phase, over the temperature range 220 to 343 K near the saturation line. The measurements in both liquid and vapor phases have been carried out with a vibrating-wire viscometer calibrated with respect to standard reference values of viscosity. It is estimated that the uncertainty of the present viscosity data is one of 0.5-1%, being limited partly by the accuracy of the available density data. The experimental data have been represented by polynomial functions of temperature for the purposes of interpolation.